2018
DOI: 10.1007/s11356-018-3053-4
|View full text |Cite
|
Sign up to set email alerts
|

Urban and rural area differences in the interaction between oxidative process elements in human femoral bone

Abstract: Elements in the human body come from contaminated food, water, and air from the living area. Bones are a marker of long-term exposure to elements and show a relationship between them. The aim of the study was to analyze the correlation between the contents of Zn, Cu, Fe, Mo, Cr, Ni, Ba, Sr, and Pb in the proximal femoral head (cancellous bone) and femoral neck (cortical bone) in rural and urban populations. The study included 96 patients who were operated on for total hip replacement (THR), acquired in a surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…It has been shown that Mo and Ni may contribute to lipid peroxidation and oxidative stress [41,42] which, according to recent studies, is significantly related to OA progression [43]. Nickel is probably absorbed through transport with interaction of Fe found in the hemoglobin and participates in oxygen transport [44,45]. In our study, statistically significant Fe-Ni correlations were observed in the spongy bone, cartilage, and infrapatellar fat pad.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…It has been shown that Mo and Ni may contribute to lipid peroxidation and oxidative stress [41,42] which, according to recent studies, is significantly related to OA progression [43]. Nickel is probably absorbed through transport with interaction of Fe found in the hemoglobin and participates in oxygen transport [44,45]. In our study, statistically significant Fe-Ni correlations were observed in the spongy bone, cartilage, and infrapatellar fat pad.…”
Section: Discussionsupporting
confidence: 71%
“…In our study, statistically significant Fe-Ni correlations were observed in the spongy bone, cartilage, and infrapatellar fat pad. Dąbrowski et al [45] also noted significantly positive Fe/Ni interaction in the bone.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These epidemiological studies link dietary Mg intake with BMD, but indicate that there is a need for further well-designed research that would include both women and men. The study conducted in Wielkopolska voivodeship, Poland, demonstrated that the lack of regular physical activity led to a decrease in Mg levels in the femoral neck samples [ 85 ]. Smokers have lower Mg levels in the femoral head and in the spongy bone of the femur than nonsmokers [ 11 , 42 , 48 ].…”
Section: Magnesium (Mg)mentioning
confidence: 99%
“…Based on available data, the P concentration in the bones does not differ in accordance with the place of residence. There is no difference in P levels between the residence of villages, and small or large cities [ 42 , 85 , 109 ]. It was found that alcohol consumption has no influence on the P concentration in the bones [ 42 , 109 ], whereas smoking habit does.…”
Section: Phosphorus (P)mentioning
confidence: 99%